Does Planning Belong to the Politics of the Past? - Barbara Czarniawska (Contemporary Economics, 2012)
According to many authors, so-called 'central planning' had disappeared from European countries by 1989. However, this is by no means certain. Many former centrally planned economies still engage in central planning, in both the private and public sectors. Moreover, there is a striking similarity between so-called 'strategic planning' in large private and public units and central planning in a small-sized economy. These similarities and differences are examined in this article using several examples, concluding with city planning. The analysis suggests that city politicians may find useful lessons in organization studies, revealing that while planning has a powerful comforting and tranquilizing function, plans, like tools, need to be abandoned when they are obsolete or cumbersome. Additionally, planners and managers may find it useful to admit that the differences between the private and public sectors are not as large as conventionally assumed and that their activities are always connected to politics.
Keywords: M00; 330; financial markets; equity capital; banking; value at risk (VaR); diversification; risk management; asset-liability management